Subtype-Based Prognostic Analysis of Cell-in-Cell Structures in Early Breast Cancer - Zhang, Xin; Niu, Zubiao; Qin, Hongquan; Fan, Jie; Wang, Manna; Zhang, Bo; Zheng, You; Gao, Lihua; Chen, Zhaolie; Tai, Yanhong; Yang, Mo; Huang, Hongyan; et al. (Frontiers in Oncology, 2019)
Though current pathological methods are greatly improved, they provide rather limited functional information. Cell-in-cell structures (CICs), arising from active cell–cell interaction, are functional surrogates of complicated cell behaviors within heterogeneous cancers. In light of this, we performed the subtype-based CIC profiling in human breast cancers by the “EML” multiplex staining method, and accessed their values as prognostic factors by Cox univariate, multivariate, and nomogram analysis. CICs were detected in cancer specimens but not in normal breast tissues. A total of five types of CICs were identified with one homotypic subtype (91%) and four heterotypic subtypes (9%). Overall CICs (oCICs) significantly associated with patient overall survival (OS) (P = 0.011) as an independent protective factor (HR = 0.423, 95% CI, 0.227–0.785; P = 0.006). Remarkably, three CICs subtypes (TiT, TiM, and MiT) were also independent prognostic factors. Among them, higher TiT, from homotypic cannibalism between tumor cells, predicted longer patient survival (HR = 0.529, 95% CI, 0.288–0.973; P = 0.04) in a way similar to that of oCICs and that (HR = 0.524, 95% CI, 0.286–0.962; P = 0.037) of heterotypic TiM (tumor cell inside macrophage); conversely, the presence of MiT (macrophage inside tumor cell) predicted a death hazard of 2.608 (95% CI, 1.344–5.063; P = 0.05). Moreover, each CIC subtype tended to preferentially affect different categories of breast cancer, with TiT (P < 0.0001) and oCICs (P = 0.008) targeting luminal B (Her2+), TiM (P = 0.011) targeting HR− (Her2+/HR− and TNBC), and MiT targeting luminal A (P = 0.017) and luminal B (Her−) (P = 0.006). Furthermore, nomogram analysis suggested that CICs impacted patient outcomes in contributions comparable (for oCICs, TiT, and TiM), or even superior (for MiT), to TNM stage and breast cancer subtype, and incorporating CICs improved nomogram performance. Together, we propose CICs profiling as a valuable way for prognostic analysis of breast cancer and that CICs and their subtypes, such as MiT, may serve as a type of novel functional markers assisting clinical practices.